Pengaruh Tata Letak Toko, Kualitas Layanan, dan Motivasi Rasional terhadap Keputusan Pembelian Konsumen - Najib Fuadi; Salihah Khairawati; Hery Sasono (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2019)
This study aims to determine the effect of Store Layout, Service Quality and Rational Motivation Against Purchase Decision. This research desaigned associative or causality. Sampling in this study using Non Probability Sampling. Methods of data collection using questionnaires, about 100 respondents. Using multiple linear regression data analysis with SPSS 17 for Windows program. Result of t test show rational motivation have a significant effect to purchase decision variable, with t value 3,973> from t value of table 1,98, then sig value. 0.000 <from 0.05. While the variable store layout and service quality showed a not significant effect on consumer purchasing decisions. Based on the F test, jointly variable store layout, service quality, and rational motivation have significant influence to purchase decision, supported by coefficient of determination (R2) equal to 0,253, which means 25,3% consumer purchasing decision influenced by variable store layout , service quality, and rational motivation. While the rest equal to 74.7% influenced by factors or other variables outside the study.